Chemical composition, nutritional evaluation and functional properties of Elaeagnus mollis Diels (Elaeagnus L.) seeds. Issue 10 (6th October 2022) - Xiaoxiao, Feng; Hua, Yufei
Abstract: Background: Elaeagnus L. seeds have high amount protein and are an important food source for humans. The chemical composition of Elaeagnus mollis Diels (Elaeagnus L.) seeds and the biochemical, nutritional, and functional properties of Elaeagnus L. seeds protein isolate (PPI) and protein fractions were studied, which is essential to the exploration of new protein sources. Results: The results indicated that Elaeagnus L. seeds contained 50.87% oil and 36.27% protein. Elaeagnus L. seeds oil was rich in unsaturated fatty acid (91.7%), especially linoleic acid, oleic acid and linolenic acid and ω ‐6/ ω ‐3 was 6.33, closest to FAO/WHO recommended ratio. Alkali protein fraction (APF, 49.82%) was predominant and was rich in Glu, Arg and Pro. Water‐soluble protein fraction (WPF) had the highest SRC of 75.35, followed by PPI (70.66). The essential amino acids of PPI and WPF compared well with FAO/WHO recommended pattern for adults (except Lys and Trp). Functional properties of proteins were found to be comparable with soybean protein isolate. Low antinutritional factors enable the utilization of the proteins in nutrition food formulations. Conclusion: This study could be beneficial for enabling the utilization of Elaeagnus L. seeds proteins in nutrition and health‐related food formulations.